Upaya Reformasi Manajemen Konflik Kemahasiswaan di UIN Sunan Kalijaga: Upaya Reformasi Manajemen Konflik Kemahasiswaan dalam Kasus Pemilwa Menuju UIN Sunan Kalijaga Word Class University” - Maragustam Maragustam (Mukaddimah: Jurnal Studi Islam, 2018)
The formation of the Student Election Committee (Pemilwa) today derived from the Student Executive Council (DEMA) through the Family of Student of UIN Sunan Kalijaga (KBMU) Number 1 at the year 2013. But with the publication of Decrees number 1741 at the year 2013, the establishment is a university leaders which the two of them have strong difference. As source of Student conflict are the existence of differences on the authority substantially between Decrees of Dirjen with KBMU. The problem to be answered is how the student conflict management, in case Pemilwa and how the sources of conflict in Pemilwa? This paper is expected to contribute the management of knowledge in higher education and practically contributing to be applied practically in this institutions regard to the student conflict management. The approach is qualitative and science conflict management. The analysis apply reduction, display, and verification of data and the instrument of research is the researcher himself through interview, participative observation and documents. The results on conflict management of pre- voting in Pemilwa with (1) a compromise, namely with the steps are as follows (a) separation, and (b) return to the existing regulations, and (2) integrative way through consensus. Conflict management of post voting (1) separation, (2) return to the existing regulations based on Rector Decree, number 204.2 of the year 2015 (3) method of conflict reduction through cooling the atmosphere. The cooling atmosphere is taken by (a) the formation of fact finding team (2) the delay of time continuously while waiting for the answers from the fact finding team, (3) to train the committee of Orma-Suka, with the note «if the fact finding team finds the violations significantly, then Orma-Suka is dimisionered by law”. Meanwhile, as source of conflict is to (1) the differences in the rules used by the students namely KBMU, number 1 at the year of 2013, while UIN Sunan Kalijaga applied the Dirjen Decrees number 1741 at the year 2013, (2) the difference of interest from Pemilwa participants in implementing Pemilwa itself , (3) the contention and competition at the limited terms, namely in membership and positions in the structure of PPUMF and PPUMU, (4) the different interpretations on the guidelines of Pemilwa especially in the technical term of opened voting or closed system, and (5) the delay in voting on the actual time namely it was started at 08.00, but in fact it was just begun at around 11:00 pm.